DELINEATION OF URBAN FLOOD RISK AREAS USING GEOSPATIAL TECHNIQUE - Yunus, Sulaiman (FUDMA JOURNAL OF SCIENCES, 2021)
The threat posed by urban flooding in most cities of the world is becoming alarming especially within the recent decades. This makes it necessary to Identify and delineate flood risk areas within cities in order to curb it menace. This study employs geospatial technique to delineate flood risk areas within Kano metropolis with a view to mitigating its impact on lives and properties. Digital Elevation Model (ASTER DEM 30m) was used to derive excess surface run-off attributes including flow direction and accumulation. Based on these attributes, flood risk areas were determined and delineated using buffer distances of 500 meters. World View image (30 cm spatial resolution) was used to identify the landuses at risk. The result from the analysis delineated flood risk areas at varying exposure levels (i.e high, moderate and low).It was evident that flood risk level within the metropolis corresponds to the pattern of surface run-off flow accumulation areas. Settlements and farmlands found within high accumulation areas along the floodplains of River Jakara (in the North and North-eastern part) and Kano-Zaria road (southern part) are at higher risk than those found on low accumulation areas. The study concluded that excess surface run-off flow direction and accumulation are among the fundamental factors determining the risk to urban flooding. The study recommends that with the ongoing level of urban development and impervious surface expansion, urban planners and policy makers should make use of the flow direction and accumulation maps in determining safer places for future developments.